PENERAPAN MODEL POLYA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Yuni Fitriani; Rusdial Marta; Zulhendri; Yanti Yandri Kusuma; Iis Aprinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the mathematical problem-solving skills of fifth-grade students at UPT SDN 016 Bukit Ranah, Kampar District, through the implementation of Polya’s instructional model. The research method employed was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were 15 students, comprising 7 boys and 8 girls, in the 2024/2025 academic year. Data collection techniques included observation, tests, and documentation, with qualitative analysis used for learning activities and quantitative analysis for students’ problem-solving test results. The findings revealed an improvement in students’ classical mastery at each stage. In Cycle I, Meeting 1, the classical mastery rate was 40%, which increased to 53% in Meeting 2. In Cycle II, Meeting 1, it rose to 87% and further increased to 93% by the end of Cycle II. This improvement indicates that Polya’s instructional model is effective in helping students understand problems, formulate solutions, carry out problem-solving steps, and draw conclusions. Therefore, it can be concluded that the implementation of Polya’s instructional model can significantly enhance the mathematical problem-solving skills of fifth-grade students at UPT SDN 016 Bukit Ranah.